Synergistic improvements in stability and performance of lead iodide perovskite solar cells incorporating salt additives - Boopathi, Karunakara Moorthy; Mohan, Ramesh; Huang, Tzu-Yen; Budiawan, Widhya; Lin, Ming-Yi; Lee, Chih-Hao; Ho, Kuo-Chuan; Chu, Chih-Wei (Journal of materials chemistry. A, Materials for energy and sustainability, 2016)
The main issues in planar perovskite solar cells are the coverage and crystallinity of the perovskite film on the PEDOT:PSS layer. To enhance these features, we introduced alkali metal halides (salts) as additives into the perovskite precursor solution used in a two-step preparation method. These alkali metal halides chelate with Pb 2+ ions and enhance the crystal growth of PbI 2 films, resulting in nanostructured morphologies. The nanostructured PbI 2 films promote homogeneous nucleation and larger crystallite sizes, thereby enhancing the morphology and crystallinity of the perovskite films. The alkali metal halides recrystallize the small grains and passivate the grain boundaries and interface states, allowing effective charge generation and dissociation in perovskite films. Photoluminescence measurements indicated that perovskite films prepared with salt additives featured fewer charge traps and defects. The power conversion efficiency of the device incorporating a small amount of a salt additive increased by approximately 33%-from 11.4 to 15.08%. This device was more stable than a corresponding device prepared without the additive, with only 16.5% degradation occurring over a period of 50 days. Alkali metal halide additives chelate with Pb 2+ ions during film formation promoting homogeneous nucleation, which greatly enhances the power conversion efficiency (15.08%) and stability (over 50 days) of planar perovskite solar cells.